Vocabulary Coverage in a High School Vietnamese EFL Textbook: A Corpus-based Preliminary Investigation (Journal of Contemporary Educational Policies and Practices, 2022)
In the context of English as a foreign language (EFL) teaching, textbooks play a crucial role in the classroom as the primary source of lexical input for learners. Thus, it is essential that textbooks can sufficiently facilitate learners in their overall comprehension and vocabulary learning, especially with the most frequent words in English. The study examined the vocabulary load of a locally-published EFL textbook in Vietnam for high school students focusing on the vocabulary coverage in relation to the 95% and 98% thresholds for text comprehension and the coverage of high-frequency word families in the textbook. To fulfil these objectives, a frequency-based analysis of word families using the Vocabprofilers on the https://www.lextutor.ca/ website was conducted with the 41,137-word textbook corpus. It is revealed that students need to have a vocabulary size of 3,000 and 5,000-word families to reach the coverage of 95% and 98% of the whole textbook, which would be too challenging for Vietnamese high school students. Moreover, the textbook was found not to represent the second 1,000-word list very well with the appearance of just over half of the second most frequent 1,000-word families. These findings highlight the role of teachers in adapting the textbook for more effective vocabulary learning and general comprehension of the materials.